Criminal woman, the prostitute, and the normal woman - Lombroso, Cesare, 1835-1909 (e-Duke books scholarly collection., 2004)
Cesare Lombroso is widely considered the founder of the field of criminology. His theory of the born criminal dominated discussions of criminology in Europe and the Americas from the 1880s into the early twentieth century. His book, La donna delinquente, originally published in Italian in 1893, was the first and most influential book ever written on women and crime. This comprehensive new translation gives readers a full view of his landmark work. Lombrosos research took him to police stations, prisons, and madhouses where he studied the tattoos, cranial capacities, and sexual behavior of criminals and prostitutes to establish a female criminal type. Criminal Woman, the Prostitute, and the Normal Womananticipated todays theories of genetic criminal behavior. Lombroso used Darwinian evolutionary science to argue that criminal women are far more cunning and dangerous than criminal men. Designed to make his original text accessible to students and scholars alike, this volume includes extensive notes, appendices, a glossary, and more than thirty of Lombrosos own illustrations. Nicole Hahn Rafter and Mary Gibsons introduction, locating his theory in social context, offers a significant new interpretation of Lombrosos place in criminology.